Evaluating the impact of the HIV pandemic on measles control and elimination - Rita F. Helfand; William J. Moss; Rafael Harpaz; Susana Scott; Felicity Cutts (The World Health Organization, 2005)
OBJECTIVE: To estimate the impact of the HIV pandemic on vaccine-acquired population immunity to measles virus because high levels of population immunity are required to eliminate transmission of measles virus in large geographical areas, and HIV infection can reduce the efficacy of measles vaccination. METHODS: A literature review was conducted to estimate key parameters relating to the potential impact of HIV infection on the epidemiology of measles in sub-Saharan Africa; parameters included the prevalence of HIV, child mortality, perinatal HIV transmission rates and protective immune responses to measles vaccination. These parameter estimates were incorporated into a simple model, applicable to regions that have a high prevalence of HIV, to estimate the potential impact of HIV infection on population immunity against measles. FINDINGS: The model suggests that the HIV pandemic should not introduce an insurmountable barrier to measles control and elimination, in part because higher rates of primary and secondary vaccine failure among HIV-infected children are counteracted by their high mortality rate. The HIV pandemic could result in a 2-3% increase in the proportion of the birth cohort susceptible to measles, and more frequent supplemental immunization activities (SIAs) may be necessary to control or eliminate measles. In the model the optimal interval between SIAs was most influenced by the coverage rate for routine measles vaccination. The absence of a second opportunity for vaccination resulted in the greatest increase in the number of susceptible children. CONCLUSION: These results help explain the initial success of measles elimination efforts in southern Africa, where measles control has been achieved in a setting of high HIV prevalence.